Changes in Blood Pressure and Arterial Hemodynamics following Living Kidney Donation - Price, Anna M. (Clin J Am Soc Nephrol, 2020)
BACKGROUND AND OBJECTIVES: The Effect of a Reduction in GFR after Nephrectomy on Arterial Stiffness and Central Hemodynamics (EARNEST) study was a multicenter, prospective, controlled study designed to investigate the associations of an isolated reduction in kidney function on BP and arterial hemodynamics. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Prospective living kidney donors and healthy controls who fulfilled criteria for donation were recruited from centers with expertise in vascular research. Participants underwent office and ambulatory BP measurement, assessment of arterial stiffness, and biochemical tests at baseline and 12 months. RESULTS: A total of 469 participants were recruited, and 306 (168 donors and 138 controls) were followed up at 12 months. In the donor group, mean eGFR was 27 ml/min per 1.73 m(2) lower than baseline at 12 months. Compared with baseline, at 12 months the mean within-group difference in ambulatory day systolic BP in donors was 0.1 mm Hg (95% confidence interval, −1.7 to 1.9) and 0.6 mm Hg (95% confidence interval, −0.7 to 2.0) in controls. The between-group difference was −0.5 mm Hg (95% confidence interval, −2.8 to 1.7; P=0.62). The mean within-group difference in pulse wave velocity in donors was 0.3 m/s (95% confidence interval, 0.1 to 0.4) and 0.2 m/s (95% confidence interval, −0.0 to 0.4) in controls. The between-group difference was 0.1 m/s (95% confidence interval, −0.2 to 0.3; P=0.49). CONCLUSIONS: Changes in ambulatory peripheral BP and pulse wave velocity in kidney donors at 12 months after nephrectomy were small and not different from controls. CLINICAL TRIAL REGISTRY NAME AND REGISTRATION NUMBER: NCT01769924 (https://clinicaltrials.gov/ct2/show/NCT01769924).